PENGEMBANGAN KETERAMPILAN SOSIAL ANAK USIA 4-5 TAHUN DALAM MODEL PEMBELAJARAN SENTRA - Hartati, Sofia; Putri, Sandy Tegariyani (Perspektif Ilmu Pendidikan, 2010)
This study aims at describing the social skills of 4-5 years’ children in learning center model. The study took place at Raudhatul Athfal (RA) of Istiqlal, Central Jakarta and focused on learning social skills of 4-5 years’ children on the basics of adaptation skill, cooperative skills, sharing skill, and communication skills. As a qualitative study, the data were collected by direct observation, interviewing teacher and headmaster, and documentation. The result of the study provided the description social skills of the 4-5 years children in the four aspects predetermined before.